Comparisons and Impacts of the Basic Components of Sarcopenia Definition and Their Pairwise Combinations in Gastric Cancer: A Large-Scale Study in a Chinese Population - Zhang, Feng-Min; Zhang, Xian-Zhong; Shi, Han-Ping; Zhang, Zhao; Wang, Su-Lin; Shen, Zi-Le; Chen, Xiao-Lei; Shen, Xian; Yu, Zhen; Zhuang, Cheng-Le (Frontiers in Nutrition, 2021)
Background and Aims: Sarcopenia is negatively associated with clinical outcomes. However, the definitions of sarcopenia are inconsistent across international consensuses. Thus, the purpose of this study is to compare the impact of the basic definition components of sarcopenia and their combinations in post-operative complications and overall survival, aiming to find the best sarcopenia definition to stratify the prognosis in an Asian population. Methods: A total of 1,307 patients who underwent curative surgery for gastric cancer from July 2014 to May 2019 were prospectively included. The basic sarcopenia components were measured pre-operatively, including low skeletal muscle mass index (LSMI), low skeletal muscle radiodensity (LSMD), low handgrip strength (LHGS), and low gait speed (LGS). Among them, LSMI and LSMD were measured using a CT post-processing software, LHGS was measured using an electronic hand dynamometer, and LGS was represented by a 6-m walk speed. Results: For the single basic component, the muscle function parameters (LHGS or LGS) but not the muscle composition parameters (LSMI or LSMD) showed associations with post-operative complications and mortality. For the combination of the basic combinations, all statistically significant combinations included at least one muscle function parameter. The combination of muscle composition (LSMI or LSMD) and muscle function (LHGS or LGS) had a significantly higher area under the curve in the prediction of post-operative complications compared with the combinations of two muscle function parameters (LSMI plus LSMD) or two muscle composition parameters (LHGS plus LGS). Conclusions: Compared with muscle composition parameters (LSMI and LSMD), muscle function parameters (LHGS and LGS) are better predictors of post-operative complications and overall survival, which should be considered as the principal determinant in the sarcopenia definition. The definition of sarcopenia consists of muscle function (LHGS or LGS) and muscle composition (LSMI or LSMD) separately, which is better than the combination of the two muscle function parameters (LHGS plus LGS) or two muscle composition parameters (LSMI plus LSMD).